(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Acinetobacter baumannii (A. baumanii) has recently emerged as a major pathogen causing nosocomial infections in patients admitted to intensive care units with a surprisingly rapid acquisition of antibiotic resistance. Objective: To study the rate of occurrence of A. baumanii isolated from different clinical specimens and to study the rate of occurrence of multidrug resistance especially NDM-1 and qnrA genes. Methods: A total of sixty-two (62) clinical isolates of A. baumanii were tested against 14 antibiotics by disc diffusion method. Minimum inhibitory concentration was determined by agar dilution method for resistant isolates. Polymerase chain reaction (PCR) was performed to detect bla NDM-1 and qnrA genes. Results: All Acinetobacter isolates were complete resistant to Colistin and Tigacycline (100%), while high rate of resistance was to Aztronem (93.54%), Cefotaxime, (91.93%), Ceftriaxone (88.70%) and Meropinem (80.64%). Moderate - to- low rate of resistance was to Ceftazidime (77.41%), Cefepim (75.80%), Peperacillin and Ciprofloxacin (74.19%), Gentamicin (69.35%), Levofloxacin (64.51%), Amikacin (61.29%) and Impenim (50%). The highest minimum inhibitory concentration value 128 ?g/mL was to Cefotaxime, Tigacycline and Colistin. While the lowest value 8 ?g/mL was to Gentamicin, Imipenem, Ciprofloxacin and Levofloxacin. The PCR results showed that 50% of Metallo beta lactamase producers A. baumannii was carried bla NDM-1 gene in chromsomal DNA and 24 (48%) of Flouroquinolone resistance A. baumannii harbored qnrA gene in chromsomal DNA while the prevalence of qnrA gene was (60.6%) in plasmid DNA. Conclusion: There is a high prevalence of multidrug resistant A. baumannii in different samples from Baghdad with the high prevalence of bla NDM-1 and qnrA genes among this bacterium. Keywords: Acinetobacter baumannii, bla NDM-1, qnrA- gene, MDR Citation: Mshachal MA, Abdulrahman TR, Khudair MS, Hassan JS. Molecular detection of multidrug resistant Acinetobacter baumannii from different clinical samples. Iraqi JMS. 2017; Vol. 15(3): 314-323. doi: 10.22578/IJMS.15.3.14